Stereotypes versus experience: Indexing regional identity in Bolivian Valley Spanish. (November 2014) - Babel, Anna M.
<x xml:space="preserve">Abstract</x> Stereotypes of highland and lowland identity categories in the Santa Cruz valleys of Bolivia are linked to phonetic variation in the Spanish discourse marker pues. Highlanders are believed to say [pwes] or [ps] while lowlanders are believed to say [pweh] or [pwe]. However, these beliefs erase two types of differences. First, they erase a distinction among highlanders. While highlanders from the Potosí‐Oruro area pronounce pues as they are believed to, highlanders from Cochabamba do not. Secondly, these beliefs erase intra‐speaker variation. Highlanders sometimes use the lowland variants of pues, and vice versa. When people use atypical pronunciations, they invoke an indexical field linked to the group associated with that variant. This indexical field references stereotypical ideas about groups even when they are inaccurate. Specifically, highland variants index 'pushy' or 'aggressive' stances, which are associated with people from Cochabamba, even though people from Cochabamba do not use highland variants of pues.